Gardzienice : Polish Theatre in Transition. - Allain, Paul (Routledge, 1998)
This is one of the first detailed attempts to assess developments in Polish experimental theatres since 1989. The author questions whether those artists can maintain their vision in the face of Poland's economic difficulties and increased.